Human disposition, metabolism and excretion of etamicastat, a reversible, peripherally selective dopamine β‐hydroxylase inhibitor. (June 2014) - Loureiro, Ana I.; Rocha, Jose F.; Fernandes‐Lopes, Carlos; Nunes, Teresa; Wright, Lyndon C.; Almeida, Luis; Soares‐da‐Silva, Patricio
<x xml:space="preserve">Abstract</x> Aims Etamicastat is a reversible dopamine‐β‐hydroxylase inhibitor that decreases noradrenaline levels in sympathetically innervated tissues and slows down sympathetic nervous system drive. In this study, the disposition, metabolism and excretion of etamicastat were evaluated following [14C]‐etamicastat dosing. Methods Healthy Caucasian males (n = 4) were enrolled in this single‐dose, open‐label study. Subjects were administered 600 mg of unlabelled etamicastat and 98 µCi weighing 0.623 mg [14C]‐etamicastat. Blood samples, urine and faeces were collected to characterize the disposition, excretion and metabolites of etamicastat. Results Eleven days after administration, 94.0% of the administered radioactivity had been excreted; 33.3 and 58.5% of the administered dose was found in the faeces and urine, respectively. Renal excretion of unchanged etamicastat and its N‐acetylated metabolite (BIA 5‐961) accounted for 20.0 and 10.7% of the dose, respectively. Etamicastat and BIA 5‐961 accounted for most of the circulating radioactivity, with a BIA 5‐961/etamicastat ratio that was highly variable both for the maximal plasma concentration (19.68–226.28%) and for the area under the plasma concentration–time curve from time zero to the last sampling time at which the concentration was above the limit of quantification (15.82– 281.71%). Alongside N‐acetylation, metabolism of etamicastat also occurs through oxidative deamination of the aminoethyl moiety, alkyl oxidation, desulfation and glucuronidation. Conclusions Etamicastat is rapidly absorbed, primarily excreted via urine, and its biotransformation occurs mainly via N‐acetylation (N‐acetyltransferase type 2), although glucuronidation, oxidation, oxidative deamination and desulfation also take place.